(untitled) (KYAMC Journal, 2017)
Coronary artery bypass grafting (CABG) is one of the procedure done worldwide with acceptable results and has the highest impact in the history of medicine. Atherosclerotic Plaque formation in the sub-intimal layer is the main pathophysiology which causes ischemia in cardiac muscle & gives symptoms of coronary artery disease (CAD). There are many ways for revascularization but CABG is the mostly performed procedure & still gold standard. Results of percutaneous coronary interventions (PCI) & other novel approach to coronary revascularization is still compared with conventional CABG. Left internal mammary artery is the most durable conduits & should be used for every patients unless contraindicated. In young non-diabetic patient as much possible arterial conduits should be used. In planned operations results are excellent with inhospital mortality <1% with few morbidities like sternal wound infection <3%, renal and neurological complications <7% & <3%. KYAMC Journal Vol. 7, No.-2, Jan 2017, Page 795-803